2010
DOI: 10.1111/j.1365-2583.2009.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the venom composition of the ectoparasitoid wasp Nasonia vitripennis from bioinformatic and proteomic studies

Abstract: With the Nasonia vitripennis genome sequences available, we attempted to determine the proteins present in venom by two different approaches. First, we searched for the transcripts of venom proteins by a bioinformatic approach using amino acid sequences of known hymenopteran venom proteins. Second, we performed proteomic analyses of crude N. vitripennis venom removed from the venom reservoir, implementing both an off-line two-dimensional liquid chromatography matrix-assisted laser desorption/ionization time-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
237
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(247 citation statements)
references
References 100 publications
4
237
1
1
Order By: Relevance
“…Previous studies have demonstrated that arthropod venoms also contain serine protease inhibitors (Yuan et al, 2008;Choo et al, 2012). The expression pattern of Bt-CI in B. terrestris observed here suggests that Bt-CI likely functions as a serine protease inhibitor in the fat body and venom (de Graaf et al, 2010). The venom duct and reservoir in honeybees are characterized by an epicuticular lining (Bridges and Owen, 2005) and endocuticular proteins in the gland tissues (Peiren et al, 2008).…”
Section: Resultssupporting
confidence: 51%
“…Previous studies have demonstrated that arthropod venoms also contain serine protease inhibitors (Yuan et al, 2008;Choo et al, 2012). The expression pattern of Bt-CI in B. terrestris observed here suggests that Bt-CI likely functions as a serine protease inhibitor in the fat body and venom (de Graaf et al, 2010). The venom duct and reservoir in honeybees are characterized by an epicuticular lining (Bridges and Owen, 2005) and endocuticular proteins in the gland tissues (Peiren et al, 2008).…”
Section: Resultssupporting
confidence: 51%
“…Wasp venom genes were proposed to encode small, classically secreted proteins (47), and this idea appears to be somewhat true of G1 venom proteins; 28% contained a predicted secretion signal, and these proteins had an average size of 44 kDa. However, venom SERCA is a large (110-kDa) transmembrane protein with no classical secretion signal sequence, and this finding was not unusual across G1 and other Hymenopteran venoms; G1 venom proteins range in size from 9 kDa to 379 kDa, and bioinformatic analyses using transmembrane domain prediction software (48) reveals that 7% (12/166) of G1 venom proteins and 20% (176/864) of the previously identified Hymenopteran venoms in GenBank (30) contain predicted transmembrane domains.…”
Section: Resultsmentioning
confidence: 99%
“…4). This type of protein is also found in the venom of several parasitoids (de Graaf et al, 2010) and CiBV protein 97b might thus also be a virulence factor. CiBV protein 13c has similarity to S-phase kinaseassociated protein 1A and its transcript increased approximately 20-fold in female pupae (Table 2, Fig.…”
Section: Cibv Gene Products With No Similarity To Viral Proteinsmentioning
confidence: 99%